Adam & Eve - Naslund, Sena Jeter (New York : William Morrow, 2010)
While searching for the true authorship of the Book of Genesis, Lucy Bergmann's plane goes down near the supposed location of the Garden of Eden, where she meets Adam, whose search for knowledge has led to madness.
Keywords: Bible. -- Authorship -- Fiction; Widows -- Fiction; Anthropologists -- Fiction; Creation -- Fiction; Soldiers -- United States -- Fiction; Iraq -- Fiction; Suspense fiction